2017
DOI: 10.1186/s12886-017-0471-x
|View full text |Cite
|
Sign up to set email alerts
|

Switch to aflibercept or ranibizumab after initial treatment with bevacizumab in eyes with neovascular AMD

Abstract: BackgroundTo evaluate changes in central macular thickness (CMT) and visual outcome in patients with neovascular age-related macular degeneration (AMD) treated initially with bevacizumab and subsequently switched to either aflibercept or ranibizumab.MethodsObservational clinical study was performed. We measured the structural outcome (CMT on SD-OCT; μm) and the visual outcome (best corrected visual acuity (BCVA); logMAR), as follows: before treatment (at baseline), following bevacizumab treatment (switch follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…5 The financial burden of different treatment regimens with anti-VEGF need to be considered whenever the decision of treatment is made. 6 To the best of our knowledge, outcome comparisons of aflibercept and ranibizumab as a second line of treatment for refractory DME after initial bevacizumab injections have not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The financial burden of different treatment regimens with anti-VEGF need to be considered whenever the decision of treatment is made. 6 To the best of our knowledge, outcome comparisons of aflibercept and ranibizumab as a second line of treatment for refractory DME after initial bevacizumab injections have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“… 5 The financial burden of different treatment regimens with anti-VEGF need to be considered whenever the decision of treatment is made. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Several small-scale studies have reported the potential benefits of switching anti-VEGF agents after poor response to first-line therapy. 51 54 In one study, Waizel et al 51 reported that switching from bevacizumab to either aflibercept or ranibizumab led to a significant decrease in mean central macular thickness at the final follow-up. However, mean BCVA only improved slightly at the final follow-up in both the aflibercept and ranibizumab groups, and there was no significant difference between switch treatment groups in both outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, mean BCVA only improved slightly at the final follow-up in both the aflibercept and ranibizumab groups, and there was no significant difference between switch treatment groups in both outcomes. 51 In a retrospective case series of 94 patients with nAMD, 68 of whom were refractory to previous bevacizumab or ranibizumab treatment (categorized by the presence of persistent intraretinal and/or subretinal fluid despite monthly injections), Yonekawa et al 52 reported visual and anatomical outcomes with switching to aflibercept treatment. In refractory patients, stabilization of visual acuity was reported after one aflibercept injection and at the final follow-up compared with visual acuity before switching to aflibercept ( P = 0.897 and P = 0.215, respectively); however, significant improvements in mean central macular thickness compared with before switching were reported at these endpoints ( P < 0.001 for both time points).…”
Section: Discussionmentioning
confidence: 99%
“…AMD can occur in dry (atrophic) or wet (exudative, neovascular) form. Dry AMD is manifested in 80–85% of all cases, but treatment options are available only to patients with wet AMD and do not address disease causes, but rely on the inhibition of vascular endothelial growth factor (VEGF) by antiangiogenic agents [6]. Aging is the most serious risk factor for AMD and the number of individuals affected increases significantly after the age of 50 years [7].…”
Section: Introductionmentioning
confidence: 99%